2008
DOI: 10.1007/s11284-008-0506-0
|View full text |Cite
|
Sign up to set email alerts
|

Mineral nutrient economy in competing species of Sphagnum mosses

Abstract: Bog vegetation, which is dominated by Sphagnum mosses, depends exclusively on aerial deposition of mineral nutrients. We studied how the main mineral nutrients are distributed between intracellular and extracellular exchangeable fractions and along the vertical physiological gradient of shoot age in seven Sphagnum species occupying contrasting bog microhabitats. While the Sphagnum exchangeable cation content decreased generally in the order Ca 2+ ‡ K + , Na + , Mg 2+ > Al 3+ > NH 4 + , intracellular element co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…The desiccation avoidance strategy is possible only when the cell walls are strong enough to prevent collapse of the large capillary spaces as discussed above. (2) Low nutrient availability in rainfed hummocks can be partly compensated by the greater CEC of hummock-forming sphagna provided by sphagnan (consistent with Clymo (1963);Painter (2003); Hájek and Adamec (2009)) as the cationic nutrients from atmospheric deposition can be retained on the cation-exchange sites before assimilation. Although CEC can be considered a measure of sphagnan, their correlation was not as high as expected, obviously due to the non-exhaustive sphagnan isolation.…”
Section: Discussionmentioning
confidence: 99%
“…The desiccation avoidance strategy is possible only when the cell walls are strong enough to prevent collapse of the large capillary spaces as discussed above. (2) Low nutrient availability in rainfed hummocks can be partly compensated by the greater CEC of hummock-forming sphagna provided by sphagnan (consistent with Clymo (1963);Painter (2003); Hájek and Adamec (2009)) as the cationic nutrients from atmospheric deposition can be retained on the cation-exchange sites before assimilation. Although CEC can be considered a measure of sphagnan, their correlation was not as high as expected, obviously due to the non-exhaustive sphagnan isolation.…”
Section: Discussionmentioning
confidence: 99%
“…A lower Sphagnum NPP may be caused by the higher biomass of vascular plants in the later regeneration stages, causing shading (Berendse et al 2001). Another possible cause is a change in species composition: early stages were dominated by the more minerotrophic species Sphagnum fallax , while other ombrotrophic species such as Sphagnum magellanicum , Sphagnum rubellum , and Sphagnum fuscum also occurred locally in site C. These changes in species composition also suggest a decrease in nutrient availability from site A to site C (Hajek & Adamec 2009; Grosvernier et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Limpens & Berendse (2003) have demonstrated growth reduction of S. magellanicum subjected to high N deposition. In addition, Hájek & Adamec (2009) found that intracellular N content was about 40% lower in S. magellanicum than in the competing species S. angustifolium . The results indicate unequal competition for N, which can lead to out‐competing of S. magellanicum from mixed patches.…”
Section: Discussionmentioning
confidence: 96%